Transcranial Laser Photobiomodulation Improves Intracellular Signaling Linked to Cell Survival, Memory and Glucose Metabolism in the Aged Brain: A Preliminary Study - Cardoso, Fabrízio dos Santos; Mansur, Fernanda Cristina Borini; Lopes-Martins, Rodrigo Álvaro Brandão; Gonzalez-Lima, Francisco; Gomes da Silva, Sérgio (Frontiers in Cellular Neuroscience, 2021)
Aging is often accompanied by exacerbated activation of cell death-related signaling pathways and decreased energy metabolism. We hypothesized that transcranial near-infrared laser may increase intracellular signaling pathways beneficial to aging brains, such as those that regulate brain cell proliferation and apoptosis and energy metabolism. To test this hypothesis, we investigated the expression and activation of intracellular signaling proteins in the cerebral cortex and hippocampus of aged rats (20 months old) treated with transcranial near-infrared laser for 58 consecutive days. As compared to sham controls, transcranial laser treatment increased intracellular signaling proteins related to cell proliferation and cell survival, such as signal transducer and activator of transcription 3 (STAT3), extracellular signal-regulated protein kinase (ERK), c-Jun N-terminal kinase (JNK), p70 ribosomal protein S6 kinase (p70S6K) and protein kinase B (PKB), also known as Akt that is linked to glucose metabolism. In addition, ERK is linked to memory, while ERK and JNK signaling pathways regulate glucose metabolism. Specifically, the laser treatment caused the activation of STAT3, ERK and JNK signaling proteins in the cerebral cortex. In the hippocampus, the laser treatment increased the expression of p70S6K and STAT3 and the activation of Akt. Taken together, the data supports the hypothesis that transcranial laser photobiomodulation improves intracellular signaling pathways linked to cell survival, memory and glucose metabolism in the brain of aged rats.